Self-repairing anti-icing corrosion-resistant integrated coating and preparation method thereof
By preparing a self-healing anti-icing and corrosion-resistant integrated coating, using the combined technology of phase change materials and photothermal polymers, the existing coatings have been solved in the problem of de-icing and corrosion-resistant performance degradation in extremely light-free environments, and the coating has been achieved self-repair and long-term protection effects.
Patent Information
- Application Number
- CN202411935972.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing anti-ice coating has de-icing and corrosion resistance in extremely light-free environments, and lacks self-repair functions, making it difficult to deal with local corrosion caused by tiny cracks or damage.
The preparation method of self-healing anti-icing and corrosion-resistant integrated coating is adopted, and anti-corrosion-resistant coating is prepared by preparing phase change heat-storage spinning liquid, electrospinning, and anti-corrosion-resistant coating, and spraying it on the surface of aluminum alloy to obtain the coating.
Active deicing through the heat storage and photothermal effect of phase change materials in extreme light-free environments is achieved, which enhances the anti-ice coating and corrosion resistance of the coating, and prevents local corrosion through the self-healing characteristics of epoxy resin, extends the service life of the coating.
Smart Images

Figure CN119775856A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional coating preparation methods, and specifically relates to a method for preparing a self-repairing anti-icing and anti-corrosion integrated coating, and also relates to a coating prepared by the preparation method. Background Art
[0002] Under extreme climatic conditions, especially in low temperature and humid environments, ice coating on the surface of metal substrates and subsequent corrosion problems are major challenges facing the industrial field today. Although there has been some progress in the anti-icing and anti-corrosion coatings on the current market, there are still some significant shortcomings. On the one hand, although methods such as simple super-hydrophobic surfaces and photothermal deicing coatings can effectively reduce ice adhesion and enhance anti-icing performance, their long-term stability in complex lightless environments is insufficient and is greatly affected by weather factors. On the other hand, these coatings have weak corrosion resistance. Although they can protect the metal substrate to a certain extent, they lack self-repairing functions and are difficult to deal with local corrosion caused by tiny cracks or damage. These corrosion phenomena will also increase their cost of use to a certain extent, limiting their widespread application.
[0003] The existing coatings are in extreme lightless environments for a long time, and the coating's photothermal deicing performance cannot function. While reducing the surface anti-icing performance, it is also unable to cope with the performance degradation problem after the coating is damaged. The anti-corrosion performance is poor, and there are also the disadvantages of not having active photothermal deicing and the problem of being unable to self-repair after the surface is damaged. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a self-repairing anti-icing and anti-corrosion integrated coating, which solves the problem that the deicing performance and anti-corrosion performance of the existing anti-icing coating decrease in a long-term extreme lightless environment.
[0005] Another object of the present invention is to provide a coating prepared by a method for preparing a self-repairing anti-icing and anti-corrosion integrated coating.
[0006] The technical solution adopted in the present invention is a method for preparing a self-repairing anti-icing and anti-corrosion integrated coating, specifically: preparing a phase change heat storage spinning solution, electrospinning the spinning solution to obtain an anti-corrosion heat storage fiber, and then sequentially preparing a photothermal polymer anti-corrosion filler and a self-repairing anti-icing and anti-corrosion coating, spraying the coating on the surface of an aluminum alloy, and obtaining a self-repairing anti-icing and anti-corrosion integrated coating after drying.
[0007] The present invention is also characterized in that:
[0008] Follow the steps below to implement it:
[0009] Step 1: Prepare phase change heat storage spinning solution
[0010] The phase change material, emulsifier, deionized water and surfactant were mixed in proportion and stirred evenly at 30°C, TEOS and catalyst were added dropwise and stirred for 2.5 hours, and the heat storage filler was obtained after washing and drying; DMF and acetone with a mass ratio of 1:1 were used as solvents, PVDF was added and stirred for 15 minutes; the heat storage filler was added to the PVDF solution, stirred at 25°C for 5 hours and allowed to stand for 0.5 hours to obtain a phase change heat storage spinning solution;
[0011] Step 2: Preparation of anti-corrosion heat storage fibers by electrospinning
[0012] The spinning solution prepared in step 1 is placed in a syringe, an aluminum plate is used as a receiving device, the spinning distance is adjusted, and the voltage, temperature, humidity and injection rate are controlled for spinning, and then dried at 70° C. for 8 hours to obtain an anti-corrosion heat storage fiber;
[0013] Step 3: Preparation of photothermal polymer anticorrosive filler
[0014] Add 0.5 mol / L pyrrole monomer and 0.02 mol / L hybridizing agent to a phosphate buffer solution at pH=7 to prepare an electrolyte, electro-deposit polypyrrole fiber on the anti-corrosion heat storage fiber prepared in step 2, adjust the current density and reaction time, and obtain a photothermal polymer anti-corrosion filler after washing and drying;
[0015] Step 4: Preparation of self-repairing anti-icing and anti-corrosion coating
[0016] The photothermal polymer anticorrosive filler, epoxy resin, solvent and fluorinated silane prepared in step 3 are mixed and stirred to evenly disperse the filler, and then a curing agent and a defoaming agent are added and stirred to evenly obtain a self-repairing anti-icing and anti-corrosion coating;
[0017] Step 5: Preparation of self-repairing anti-icing and anti-corrosion integrated coating
[0018] Add the coating in step 4 to the spray gun, and slowly and evenly spray it at an angle of 60° on the surface of the aluminum alloy that has been cleaned and dried with acetone. After drying after spraying, a self-repairing, anti-icing, and anti-corrosion integrated coating can be obtained.
[0019] The heat storage filler in step 1 is composed of the following substances in mass percentage: phase change material 10% to 20%, emulsifier 5% to 15%, surfactant 3% to 10%, TEOS 7% to 15%, catalyst 1% to 5%, deionized water 35% to 74%, the sum of the above components is 100%, the mass fraction of PVDF is 8% to 15%, and the mass ratio of the heat storage filler to the PVDF solution is 1:25 to 100.
[0020] In step 1, the phase change material is any one of n-tetradecane, dodecane, and decanol, the emulsifier is a complex of tween-80 and span-80 in a mass ratio of 1:1, the surfactant is any one of PVA and CTAB, and the catalyst is one of acetic acid or ammonia water.
[0021] The volume of the syringe in step 2 is 10 mL, the distance between the receiving device and the needle is 15 cm to 20 cm, the voltage is 10 kV to 20 kV, the rate at which the needle ejects the spinning solution is 0.1 mL / h to 1.0 mL / h, the temperature is 25 ° C, the humidity during the spinning process is controlled at 30% to 50%, and the diameter of the anti-corrosion heat storage fiber is 5 μm to 10 μm.
[0022] The hybridizing agent in step 3 is NSA, and the current density is 0.9 mA / cm 2 , the reaction time is 7 minutes, and the diameter of the deposited polypyrrole fibers is 100nm~300nm.
[0023] In step 4, the self-repairing anti-icing and anti-corrosion coating is composed of the following substances in mass percentage: 1% to 10% photothermal polymer anti-corrosion filler, 1% to 10% fluorine-containing silane, 25% to 35% epoxy resin, 0.5% to 1% curing agent, 0.5% to 1% defoaming agent, 43% to 72% solvent, and the sum of the above components is 100%.
[0024] In step 4, the solvent is any one of ethanol, dimethyl sulfoxide, dimethylformamide, and N-methylpyrrolidone, the fluorinated silane is any one of hexafluoro-1,1,2,2-tetrahydrodecyltrimethoxysilane, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and heptadecafluorodecyltrimethoxysilane, the curing agent is any one of N3390 curing agent and tertiary amine, and the defoaming agent is any one of fatty alcohol ethoxysiloxane and polyether siloxane.
[0025] Another technical solution adopted by the present invention is to prepare a coating using a method for preparing a self-repairing anti-icing and anti-corrosion integrated coating.
[0026] The beneficial effects of the present invention are:
[0027] The preparation method of the self-repairing anti-icing and anti-corrosion integrated coating of the present invention is that the photothermal polymer can perform active photothermal effect de-icing when exposed to sunlight; it cooperates with the phase change material to store most of the absorbed heat inside the phase change material, and even in an extreme environment without sunlight after being exposed to light, the phase change material can actively release heat to melt ice; after adding fluorinated silane, the surface produces super-hydrophobic properties, which greatly reduces the probability of icing; PVDF fiber can provide the coating with strong corrosion resistance; epoxy resin provides the coating with a certain repair ability while preventing local corrosion, thereby further improving the corrosion resistance of the coating, and has important application prospects in the field of anti-icing. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the morphology of the self-repairing anti-icing and anti-corrosion integrated coating prepared by the present invention. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with specific implementation modes and accompanying drawings.
[0030] The preparation method of the self-repairing anti-icing and anti-corrosion integrated coating of the present invention is specifically implemented according to the following steps:
[0031] Step 1: Prepare phase change heat storage spinning solution
[0032] The phase change material, emulsifier, deionized water and surfactant were mixed in proportion and stirred evenly at 30°C, TEOS and catalyst were added dropwise and stirred for 2.5 hours, and the heat storage filler was obtained after washing and drying; DMF and acetone with a mass ratio of 1:1 were used as solvents, PVDF was added and stirred for 15 minutes; the heat storage filler was added to the PVDF solution, stirred at 25°C for 5 hours and allowed to stand for 0.5 hours to obtain a phase change heat storage spinning solution;
[0033] The heat storage filler in step 1 is composed of the following substances by mass percentage: phase change material 10% to 20%, emulsifier 5% to 15%, surfactant 3% to 10%, TEOS 7% to 15%, catalyst 1% to 5%, deionized water 35% to 74%, the sum of the above components is 100%, the mass fraction of PVDF is 8% to 15%, and the mass ratio of the heat storage filler to the PVDF solution is 1:25 to 100;
[0034] In step 1, the phase change material is any one of n-tetradecane, dodecane, and decanol, the emulsifier is a complex of tween-80 and span-80 in a mass ratio of 1:1, the surfactant is any one of PVA and CTAB, and the catalyst is one of acetic acid or ammonia;
[0035] Step 2: Preparation of anti-corrosion heat storage fibers by electrospinning
[0036] The spinning solution prepared in step 1 is placed in a syringe, an aluminum plate is used as a receiving device, the spinning distance is adjusted, and the voltage, temperature, humidity and injection rate are controlled for spinning, and then dried at 70° C. for 8 hours to obtain an anti-corrosion heat storage fiber;
[0037] The volume of the syringe in step 2 is 10 mL, the distance between the receiving device and the needle is 15 cm to 20 cm, the voltage is 10 kV to 20 kV, the rate at which the needle ejects the spinning solution is 0.1 mL / h to 1.0 mL / h, the temperature is 25 ° C, the humidity during the spinning process is controlled at 30% to 50%, and the diameter of the anti-corrosion heat storage fiber is 5 μm to 10 μm;
[0038] Step 3: Preparation of photothermal polymer anticorrosive filler
[0039] Add 0.5 mol / L pyrrole monomer and 0.02 mol / L hybridizing agent to a phosphate buffer solution at pH=7 to prepare an electrolyte, electro-deposit polypyrrole fiber on the anti-corrosion heat storage fiber prepared in step 2, adjust the current density and reaction time, and obtain a photothermal polymer anti-corrosion filler after washing and drying;
[0040] The hybridizing agent in step 3 is NSA (β-naphthalenesulfonic acid hybridizing agent), and the current density is 0.9 mA / cm 2 , the reaction time is 7 min, and the diameter of the deposited polypyrrole fibers is 100 nm to 300 nm;
[0041] Step 4: Preparation of self-repairing anti-icing and anti-corrosion coating
[0042] The photothermal polymer anticorrosive filler, epoxy resin, solvent and fluorinated silane prepared in step 3 are mixed and stirred to evenly disperse the filler, and then a curing agent and a defoaming agent are added and stirred to evenly obtain a self-repairing anti-icing and anti-corrosion coating;
[0043] In step 4, the self-repairing anti-icing and anti-corrosion coating is composed of the following substances by mass percentage: 1% to 10% of photothermal polymer anti-corrosion filler, 1% to 10% of fluorine-containing silane, 25% to 35% of epoxy resin, 0.5% to 1% of curing agent, 0.5% to 1% of defoaming agent, 43% to 72% of solvent, and the sum of the above components is 100%;
[0044] In step 4, the solvent is any one of ethanol, dimethyl sulfoxide, dimethylformamide, and N-methylpyrrolidone, the fluorinated silane is any one of hexafluoro-1,1,2,2-tetrahydrodecyltrimethoxysilane, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and heptadecafluorodecyltrimethoxysilane, the curing agent is any one of N3390 curing agent, tertiary amine, etc., and the defoaming agent is any one of fatty alcohol ethoxysiloxane and polyether siloxane;
[0045] Step 5: Preparation of self-repairing anti-icing and anti-corrosion integrated coating
[0046] Add the coating in step 4 to the spray gun, and slowly and evenly spray it at an angle of 60° on the surface of the aluminum alloy that has been cleaned and dried with acetone. After drying after spraying, a self-repairing, anti-icing, and anti-corrosion integrated coating can be obtained.
[0047] The present invention prepares heat storage fillers by adding phase change materials to enhance the ice melting ability of the coating. The amount of heat storage / release and the phase change point of the coating can be regulated by selecting different phase change materials and controlling their dosage. The phase change heat storage fillers are stored inside the PVDF fiber tissue through an electrostatic spinning process to enhance the corrosion resistance of the coating under strong acid, strong alkali and other conditions. The incompatibility of PVDF and SiO2 can ensure that the sol-gel reaction of fluorinated silane and TEOS can form a stable super-hydrophobic surface on the outside of the fiber, greatly reducing the probability of ice coating on the substrate and improving the ice melting efficiency. And the self-repairing properties of epoxy resin can also prevent local corrosion caused by micro cracking to a certain extent. By electro-depositing a polypyrrole fiber layer with a photothermal effect on the surface of PVDF, while solving the problem of the heat source of the phase change material, adding a sulfonic acid hybridizing agent can improve the orderliness of the polypyrrole fiber to block the corrosive medium, and the F element in PVDF and fluorinated silane is doped in polypyrrole as a larger hydrophobic anion, which can greatly improve the service life of the self-repairing anti-icing and anti-corrosion integrated coating.
[0048] Example 1
[0049] The preparation method of the self-repairing anti-icing and anti-corrosion integrated coating of the present invention is specifically as follows:
[0050] Step 1, according to the mass percentage: 10% dodecane, 5% tween-80 and span-80 complex with a mass ratio of 1:1, 3% PVA, 7% TEOS, 1% acetic acid, and 74% deionized water, dodecane, tween-80 and span-80 complex with a mass ratio of 1:1, deionized water and PVA are mixed and stirred evenly at 30°C, TEOS and acetic acid are added dropwise and stirred for 2.5 hours, and the heat storage filler is obtained after washing and drying; DMF and acetone with a mass ratio of 1:1 are used as solvents, PVDF with a mass fraction of 8% is added and stirred for 15 minutes; and then the heat storage filler is added to the PVDF solution at a mass ratio of 1:25 to the PVDF solution, stirred at 25°C for 5 hours and allowed to stand for 0.5 hours to obtain a phase change heat storage spinning solution;
[0051] Step 2, put the phase change heat storage spinning solution into a 10mL syringe, use an aluminum plate as a receiving device, 15cm away from the syringe needle, eject the spinning solution at a rate of 0.2mL / h at a voltage of 10kV, and keep spinning at 25°C and 30% humidity, then dry at 70°C for 8h to obtain an anti-corrosion heat storage fiber with a diameter of 5μm;
[0052] Step 3: Add 0.5 mol / L pyrrole monomer and 0.02 mol / L β-naphthalenesulfonic acid to a phosphate buffer solution at pH = 7 to prepare an electrolyte, and electrodeposit polypyrrole fiber on the anti-corrosion heat storage fiber at 0.9 mA / cm 2 The reaction was carried out at a current density of 7 min, and after washing and drying, a photothermal polymer anticorrosive filler with a polypyrrole fiber diameter of 100 nm was obtained;
[0053] Step 4, according to the mass percentage: 1% of the photothermal polymer anticorrosive filler, 1% of hexafluoro-1,1,2,2-tetrahydrodecyltrimethoxysilane, 25% of the epoxy resin, 0.5% of the N3390 curing agent, 0.5% of the fatty alcohol ethoxysiloxane, and 72% of the ethanol, mixing and stirring to evenly disperse the filler, and obtaining a self-repairing anti-icing and anti-corrosion coating;
[0054] Step 5: Add the self-repairing anti-icing and anti-corrosion coating to the spray gun, and slowly and evenly spray it on the surface of the aluminum alloy after cleaning and drying with acetone at an angle of 60°. After drying after spraying, a self-repairing anti-icing and anti-corrosion integrated coating can be obtained.
[0055] Example 2
[0056] The preparation method of the self-repairing anti-icing and anti-corrosion integrated coating of the present invention is specifically as follows:
[0057] Step 1, according to the mass percentage: 20% of n-tetradecane, 15% of tween-80 and span-80 complex with a mass ratio of 1:1, 10% of CTAB, 15% of TEOS, 5% of ammonia water, and 35% of deionized water. Mix n-tetradecane, 1:1 tween-80 and span-80 complex, deionized water and CTAB, stir evenly at 30°C, then drop TEOS and ammonia water and stir for 2.5 hours, wash and dry to obtain a heat storage filler. Use DMF and acetone with a mass ratio of 1:1 as solvent, add PVDF with a mass fraction of 15% and stir for 15 minutes. Then add the heat storage filler to the PVDF solution at a mass ratio of 1:100, stir at 25°C for 5 hours and let stand for 0.5 hours to obtain a phase change heat storage spinning solution;
[0058] Step 2, put the phase change heat storage spinning solution into a 10mL syringe, use an aluminum plate as a receiving device, and place it 20cm away from the syringe needle. Eject the spinning solution at a rate of 1.0mL / h at a voltage of 20kV. Keep spinning at 25°C and 50% humidity, then dry at 70°C for 8h to obtain an anti-corrosion heat storage fiber with a diameter of 10μm.
[0059] Step 3: Add 0.5 mol / L pyrrole monomer and 0.02 mol / L β-naphthalenesulfonic acid to a phosphate buffer solution at pH = 7 to prepare an electrolyte, and electrodeposit polypyrrole fiber on the anti-corrosion heat storage fiber at 0.9 mA / cm 2 The reaction was carried out at a current density of 7 minutes, and after washing and drying, a photothermal polymer anticorrosive filler with a polypyrrole fiber diameter of 300 nm was obtained.
[0060] Step 4, according to the mass percentage: 10% of the photothermal polymer anticorrosive filler, 10% of heptadecafluorodecyltrimethoxysilane, 35% of the epoxy resin, 1% of the tertiary amine, 1% of the polyether siloxane, and 43% of N-methylpyrrolidone, mixing and stirring to evenly disperse the filler to obtain a self-repairing anti-icing and anti-corrosion coating;
[0061] Step 5: Add the self-repairing anti-icing and anti-corrosion coating to the spray gun, and slowly and evenly spray it on the surface of the aluminum alloy after cleaning and drying with acetone at an angle of 60°. After drying after spraying, a self-repairing anti-icing and anti-corrosion integrated coating can be obtained.
[0062] Example 3
[0063] The preparation method of the self-repairing anti-icing and anti-corrosion integrated coating of the present invention is specifically as follows:
[0064] Step 1, according to the mass percentage: 15% of n-tetradecane, 10% of tween-80 and span-80 complex with a mass ratio of 1:1, 6% of PVA, 10% of TEOS, 4% of acetic acid, and 55% of deionized water. Mix n-tetradecane, 1:1 tween-80 and span-80 complex, deionized water and PVA, and stir evenly at 30°C, then drop TEOS and acetic acid and stir for 2.5 hours, wash and dry to obtain a heat storage filler. Use DMF and acetone with a mass ratio of 1:1 as solvent, add PVDF with a mass fraction of 13% and stir for 15 minutes. Then add the heat storage filler to the PVDF solution at a mass ratio of 1:50, stir at 25°C for 5 hours and let stand for 0.5 hours to obtain a phase change heat storage spinning solution;
[0065] Step 2, put the phase change heat storage spinning solution into a 10mL syringe, use an aluminum plate as a receiving device, and place it 17cm away from the syringe needle. Eject the spinning solution at a rate of 0.5mL / h at a voltage of 15kV. Keep spinning at 25°C and 45% humidity, then dry at 70°C for 8h to obtain an anti-corrosion heat storage fiber with a diameter of 6μm.
[0066] Step 3: Add 0.5 mol / L pyrrole monomer and 0.02 mol / L β-naphthalenesulfonic acid to a phosphate buffer solution at pH = 7 to prepare an electrolyte, and electrodeposit polypyrrole fiber on the anti-corrosion heat storage fiber at 0.9 mA / cm 2 The reaction was carried out at a current density of 7 min, and after washing and drying, a photothermal polymer anticorrosive filler with a polypyrrole fiber diameter of 200 nm was obtained;
[0067] Step 4, according to the mass percentage: 8% of photothermal polymer anticorrosive filler, 8% of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, 34% of epoxy resin, 0.5% of tertiary amine, 0.5% of polyether siloxane, and 49% of dimethylformamide, mixing and stirring to evenly disperse the filler to obtain a self-repairing anti-icing and anti-corrosion coating;
[0068] Step 5: Add the self-repairing anti-icing and anti-corrosion coating to the spray gun, and slowly and evenly spray it on the surface of the aluminum alloy after cleaning and drying with acetone at an angle of 60°. After drying after spraying, a self-repairing anti-icing and anti-corrosion integrated coating can be obtained.
[0069] Example 4
[0070] The preparation method of the self-repairing anti-icing and anti-corrosion integrated coating of the present invention is specifically as follows:
[0071] Step 1, according to the mass percentage: 12% decanol, 12% tween-80 and span-80 complex with a mass ratio of 1:1, 7% CTAB, 8% TEOS, 3% acetic acid, 58% deionized water, decanol, 1:1 tween-80 and span-80 complex, deionized water and CTAB are mixed and stirred evenly at 30°C, and then TEOS and acetic acid are added dropwise and stirred for 2.5 hours, and the heat storage filler is obtained after washing and drying. DMF and acetone with a mass ratio of 1:1 are used as solvents, and PVDF with a mass fraction of 11% is added and stirred for 15 minutes. Then, the heat storage filler is added to the PVDF solution at a mass ratio of 1:75 to the PVDF solution, stirred at 25°C for 5 hours and allowed to stand for 0.5 hours to obtain a phase change heat storage spinning solution;
[0072] Step 2, transfer the spinning solution into a 10mL syringe, use an aluminum plate as a receiving device, and place it 15cm away from the syringe needle. Eject the spinning solution at a rate of 0.8mL / h at a voltage of 15kV. Keep spinning at 25°C and 40% humidity, then dry at 70°C for 8h to obtain an anti-corrosion heat storage fiber with a diameter of 7μm.
[0073] Step 3: Add 0.5 mol / L pyrrole monomer and 0.02 mol / L β-naphthalenesulfonic acid to a phosphate buffer solution at pH = 7 to prepare an electrolyte, and electrodeposit polypyrrole fiber on the anti-corrosion heat storage fiber at 0.9 mA / cm 2 The reaction was carried out at a current density of 7 min, and after washing and drying, a photothermal polymer anticorrosive filler with a polypyrrole fiber diameter of 300 nm was obtained;
[0074] Step 4, according to the mass percentage: 7% of photothermal polymer anticorrosive filler, 6% of heptadecafluorodecyl trimethoxysilane, 30% of epoxy resin, 1% of N3390 curing agent, 1% of fatty alcohol ethoxysiloxane, and 55% of dimethyl sulfoxide, mixing and stirring to evenly disperse the filler to obtain a self-repairing anti-icing and anti-corrosion coating;
[0075] Step 5: Add the self-repairing anti-icing and anti-corrosion coating to the spray gun, and slowly and evenly spray it on the surface of the aluminum alloy after cleaning and drying with acetone at an angle of 60°. After drying after spraying, a self-repairing anti-icing and anti-corrosion integrated coating can be obtained.
[0076] Example 5
[0077] The preparation method of the self-repairing anti-icing and anti-corrosion integrated coating of the present invention is specifically as follows:
[0078] Step 1, according to the mass percentage: 12% of n-tetradecane, 12% of tween-80 and span-80 complex with a mass ratio of 1:1, 7% of CTAB, 8% of TEOS, 3% of acetic acid, and 58% of deionized water. Mix n-tetradecane, 1:1 tween-80 and span-80 complex, deionized water and CTAB, stir evenly at 30°C, then drop TEOS and acetic acid and stir for 2.5 hours, wash and dry to obtain a heat storage filler. Use DMF and acetone with a mass ratio of 1:1 as solvent, add PVDF with a mass fraction of 11% and stir for 15 minutes. Then add the heat storage filler to the PVDF solution at a mass ratio of 1:75, stir at 25°C for 5 hours and let stand for 0.5 hours to obtain a phase change heat storage spinning solution;
[0079] Step 2, transfer the spinning solution into a 10mL syringe, use an aluminum plate as a receiving device, and place it 15cm away from the syringe needle. Eject the spinning solution at a rate of 0.8mL / h at a voltage of 15kV. Keep spinning at 25°C and 40% humidity, then dry at 70°C for 8h to obtain an anti-corrosion heat storage fiber with a diameter of 7μm.
[0080] Step 3: Add 0.5 mol / L pyrrole monomer and 0.02 mol / L β-naphthalenesulfonic acid to a phosphate buffer solution at pH = 7 to prepare an electrolyte, and electrodeposit polypyrrole fiber on the anti-corrosion heat storage fiber at 0.9 mA / cm 2 The reaction was carried out at a current density of 7 min, and after washing and drying, a photothermal polymer anticorrosive filler with a polypyrrole fiber diameter of 300 nm was obtained;
[0081] Step 4, according to the mass percentage: 7% of photothermal polymer anticorrosive filler, 6% of heptadecafluorodecyl trimethoxysilane, 30% of epoxy resin, 1% of N3390 curing agent, 1% of fatty alcohol ethoxysiloxane, and 55% of dimethyl sulfoxide, mixing and stirring to evenly disperse the filler to obtain a self-repairing anti-icing and anti-corrosion coating;
[0082] Step 5: Add the self-repairing anti-icing and anti-corrosion coating to the spray gun, and slowly and evenly spray it on the surface of the aluminum alloy after cleaning and drying with acetone at an angle of 60°. After drying after spraying, a self-repairing anti-icing and anti-corrosion integrated coating can be obtained.
[0083] Example 6
[0084] The preparation method of the self-repairing anti-icing and anti-corrosion integrated coating of the present invention is specifically as follows:
[0085] Step 1, according to the mass percentage: 12% decanol, 12% tween-80 and span-80 complex with a mass ratio of 1:1, 7% CTAB, 8% TEOS, 3% acetic acid, 58% deionized water, decanol, 1:1 tween-80 and span-80 complex, deionized water and CTAB are mixed and stirred evenly at 30°C, and then TEOS and acetic acid are added dropwise and stirred for 2.5 hours, and the heat storage filler is obtained after washing and drying. DMF and acetone with a mass ratio of 1:1 are used as solvents, and PVDF with a mass fraction of 11% is added and stirred for 15 minutes. Then, the heat storage filler is added to the PVDF solution at a mass ratio of 1:75 to the PVDF solution, stirred at 25°C for 5 hours and allowed to stand for 0.5 hours to obtain a phase change heat storage spinning solution;
[0086] Step 2, put the phase change heat storage spinning solution into a 10mL syringe, use an aluminum plate as a receiving device, and place it 20cm away from the syringe needle. Eject the spinning solution at a rate of 1.0mL / h at a voltage of 20kV. Keep spinning at 25°C and 50% humidity, then dry at 70°C for 8h to obtain an anti-corrosion heat storage fiber with a diameter of 10μm.
[0087] Step 3: Add 0.5 mol / L pyrrole monomer and 0.02 mol / L β-naphthalenesulfonic acid to a phosphate buffer solution at pH = 7 to prepare an electrolyte, and electrodeposit polypyrrole fiber on the anti-corrosion heat storage fiber at 0.9 mA / cm 2 The reaction was carried out at a current density of 7 min, and after washing and drying, a photothermal polymer anticorrosive filler with a polypyrrole fiber diameter of 300 nm was obtained;
[0088] Step 4, according to the mass percentage: 7% of photothermal polymer anticorrosive filler, 6% of heptadecafluorodecyl trimethoxysilane, 30% of epoxy resin, 1% of N3390 curing agent, 1% of fatty alcohol ethoxysiloxane, and 55% of dimethyl sulfoxide, mixing and stirring to evenly disperse the filler to obtain a self-repairing anti-icing and anti-corrosion coating;
[0089] Step 5: Add the self-repairing anti-icing and anti-corrosion coating to the spray gun, and slowly and evenly spray it on the surface of the aluminum alloy after cleaning and drying with acetone at an angle of 60°. After drying after spraying, a self-repairing anti-icing and anti-corrosion integrated coating can be obtained.
[0090] Table 1 compares the contact angle, ice adhesion, photothermal ice-melting time, light-free ice-melting time after one photothermal ice-melting, surface contact resistance, and ice adhesion after 30 freeze / thaw cycles of the coatings prepared in Examples 1-4.
[0091] Table 1
[0092]
[0093]
[0094] As can be seen from Table 1, the water contact angle of the coating modified by photothermal modification using only polypyrrole is the smallest, and the ice adhesion is the largest. Since the heat converted by photothermal conversion is all used for deicing, the initial photothermal ice melting time is the shortest, but the subsequent lightless ice melting has the longest ice melting time due to the extremely small amount of stored heat, and the ice adhesion after cyclic freezing / thawing is the highest and increases greatly; the coating contact angle in Example 3 is the largest, and the ice adhesion is greatly reduced due to hydrophobic modification. The phase change material increases the initial photothermal ice melting time and stores a large amount of heat, so it can still maintain a shorter ice melting time in the subsequent lightless ice melting period, and the ice adhesion after continuous freezing / thawing does not change much and remains at a low level.
[0095] Table 2 is a comparison of the surface contact resistance and mass loss rate of the coatings prepared in Examples 1-4.
[0096] Table 2
[0097]
[0098]
[0099] It can be seen from Table 2 that the photothermal coating modified with polypyrrole alone has the largest surface contact resistance and the largest mass loss rate, while the coating in Example 3 exerts the anti-corrosion effect of PVDF, polypyrrole and epoxy resin. PVDF has strong corrosion resistance and can enhance the stability of polypyrrole, and the self-healing property of epoxy resin can reduce the surface damage rate and enhance the corrosion resistance. Therefore, the surface contact resistance and mass loss rate are the smallest.
[0100] Figure 1 Schematic diagram of the self-repairing anti-icing and anti-corrosion integrated coating prepared by the present invention. Figure 1 It can be seen that SiO2 gathers on the outer surface of the anti-corrosion heat storage fiber to form a super-hydrophobic interface, which weakens the ice adhesion strength. The photothermal layer composed of polypyrrole fibers grows on the surface of the coating and ensures sufficient sunlight. From the cross-sectional view of the anti-corrosion heat storage fiber, it can be seen that the phase change material is encapsulated inside the PVDF fiber, which can ensure the anti-corrosion performance of the coating while storing heat.
[0101] The present invention can perform active photothermal deicing through the photothermal polymer when exposed to sunlight; it can cooperate with the phase change material to store most of the absorbed heat inside the phase change material, and even in an extreme environment without sunlight after being exposed to light, the phase change material can actively release heat to melt ice; after adding fluorinated silane, the surface produces super-hydrophobic properties, which greatly reduces the probability of icing; PVDF fiber can provide the coating with strong corrosion resistance; epoxy resin provides the coating with a certain repair ability while preventing local corrosion, thereby further improving the corrosion resistance of the coating, and has important application prospects in the field of anti-icing.
Claims
1. A method for preparing a self-repairing anti-icing and anti-corrosion integrated coating, characterized in that: Specifically, a phase change heat storage spinning solution is prepared, the spinning solution is electrospun to obtain an anti-corrosion heat storage fiber, and then photothermal polymer anti-corrosion filler and self-repairing anti-icing and anti-corrosion coating are prepared in sequence, the coating is sprayed on the surface of aluminum alloy, and after drying, a self-repairing anti-icing and anti-corrosion integrated coating is obtained.
2. The method for preparing the self-repairing anti-icing and anti-corrosion integrated coating according to claim 1, characterized in that: Follow the steps below to implement it: Step 1: Prepare phase change heat storage spinning solution The phase change material, emulsifier, deionized water and surfactant were mixed in proportion and stirred evenly at 30°C, TEOS and catalyst were added dropwise and stirred for 2.5 hours, and the heat storage filler was obtained after washing and drying; DMF and acetone with a mass ratio of 1:1 were used as solvents, PVDF was added and stirred for 15 minutes; the heat storage filler was added to the PVDF solution, stirred at 25°C for 5 hours and allowed to stand for 0.5 hours to obtain a phase change heat storage spinning solution; Step 2: Preparation of anti-corrosion heat storage fibers by electrospinning The spinning solution prepared in step 1 is placed in a syringe, an aluminum plate is used as a receiving device, the spinning distance is adjusted, and the voltage, temperature, humidity and injection rate are controlled for spinning, and then dried at 70° C. for 8 hours to obtain an anti-corrosion heat storage fiber; Step 3: Preparation of photothermal polymer anticorrosive filler Add 0.5 mol / L pyrrole monomer and 0.02 mol / L hybridizing agent to a phosphate buffer solution at pH=7 to prepare an electrolyte, electro-deposit polypyrrole fiber on the anti-corrosion heat storage fiber prepared in step 2, adjust the current density and reaction time, and obtain a photothermal polymer anti-corrosion filler after washing and drying; Step 4: Preparation of self-repairing anti-icing and anti-corrosion coating The photothermal polymer anticorrosive filler, epoxy resin, solvent and fluorinated silane prepared in step 3 are mixed and stirred to evenly disperse the filler, and then a curing agent and a defoaming agent are added and stirred to evenly obtain a self-repairing anti-icing and anti-corrosion coating; Step 5: Preparation of self-repairing anti-icing and anti-corrosion integrated coating Add the coating in step 4 to the spray gun, and slowly and evenly spray it at an angle of 60° on the surface of the aluminum alloy that has been cleaned and dried with acetone. After drying after spraying, a self-repairing, anti-icing, and anti-corrosion integrated coating can be obtained.
3. The method for preparing the self-repairing anti-icing and anti-corrosion integrated coating according to claim 2, characterized in that: The heat storage filler in step 1 is composed of the following substances in percentage by mass: 10% to 20% phase change material, 5% to 15% emulsifier, 3% to 10% surfactant, 7% to 15% TEOS, 1% to 5% catalyst, 35% to 74% deionized water, the sum of the above components is 100%, the mass fraction of PVDF is 8% to 15%, and the mass ratio of the heat storage filler to the PVDF solution is 1:25 to 100.
4. The method for preparing the self-repairing anti-icing and anti-corrosion integrated coating according to claim 2, characterized in that: In step 1, the phase change material is any one of n-tetradecane, dodecane, and decanol, the emulsifier is a complex of tween-80 and span-80 in a mass ratio of 1:1, the surfactant is any one of PVA and CTAB, and the catalyst is one of acetic acid or ammonia water.
5. The method for preparing the self-repairing anti-icing and anti-corrosion integrated coating according to claim 2, characterized in that: The volume of the syringe in step 2 is 10 mL, the distance between the receiving device and the needle is 15 cm to 20 cm, the voltage is 10 kV to 20 kV, the rate at which the needle ejects the spinning solution is 0.1 mL / h to 1.0 mL / h, the temperature is 25°C, the humidity during the spinning process is controlled at 30% to 50%, and the diameter of the anti-corrosion heat storage fiber is 5 μm to 10 μm.
6. The method for preparing the self-repairing anti-icing and anti-corrosion integrated coating according to claim 2, characterized in that: The hybridizing agent in step 3 is NSA, and the current density is 0.9 mA / cm 2 , the reaction time is 7 minutes, and the diameter of the deposited polypyrrole fibers is 100nm~300nm.
7. The method for preparing the self-repairing anti-icing and anti-corrosion integrated coating according to claim 2, characterized in that: In step 4, the self-repairing anti-icing and anti-corrosion coating is composed of the following substances in percentage by mass: 1% to 10% of photothermal polymer anti-corrosion filler, 1% to 10% of fluorine-containing silane, 25% to 35% of epoxy resin, 0.5% to 1% of curing agent, 0.5% to 1% of defoaming agent, and 43% to 72% of solvent, and the sum of the above components is 100%.
8. The method for preparing the self-repairing anti-icing and anti-corrosion integrated coating according to claim 2, characterized in that: In step 4, the solvent is any one of ethanol, dimethyl sulfoxide, dimethylformamide, and N-methylpyrrolidone, the fluorinated silane is any one of hexafluoro-1,1,2,2-tetrahydrodecyltrimethoxysilane, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and heptadecafluorodecyltrimethoxysilane, the curing agent is any one of N3390 curing agent and tertiary amine, and the defoaming agent is any one of fatty alcohol ethoxysiloxane and polyether siloxane.
9. A coating prepared according to the method for preparing a self-repairing anti-icing and anti-corrosion integrated coating according to any one of claims 1 to 8.
Citation Information
Patent Citations
Nano-cellulose-based self-fusion photo-thermal phase change composite fiber as well as preparation method and application thereof
CN117661147A
Aluminum alloy self-repairing photo-thermal anti-icing coating and preparation method thereof
CN118879182A
Photo-thermal and electric-heating anti-icing and deicing super-hydrophobic coating and preparation method thereof
CN119060608A
Novel materials and methods for photothermal membrane distillation
US20210023505A1
Polypyrrole encapsulated graphene corrosion inhibitor container and its preparation method and composite coating and its application
US20230312939A1